Looking for More from Adjustment : Africa's Experience - Pape, Elizabeth (World Bank, Washington, DC, 2012)
By the mid-1990s, after more than 15 years of adjustment lending, it had become clear that adjustment programs in Africa had not accelerated growth or reduced poverty, except in a handful of countries. The main reasons? Recipient governments did not "own" the reform programs, and they perceived the conditionality attached to the programs as being imposed on them. Adjustment programs were often unresponsive to country conditions and changes in external circumstances. In most cases the World Bank and recipient governments did not have a shared vision of what adjustment programs were supposed to achieve. In response to this diagnosis, in 1995 the Bank's Africa Region introduced the Higher Impact Adjustment Lending (HIAL) initiative. The initiative aimed to achieve a quicker, stronger, broader, and longer supply response from structural adjustment programs by: 1) increasing country selectivity and strengthening government ownership; 2) allowing more flexibility in adjustment operations--in particular, introducing new tranching mechanisms; and 3) introducing performance indicators to define expected results and assess actual outcomes. This note describes how the approach and design of these operations were adapted to achieve higher impact.